Legal Protection of Flat Buyers Whose Land is Actually Being Secured with Hak Tanggungan - Shandy, Karina (NORMA, 2021)
The study, entitled legal protection of flat buyers whose land is actually being secured with Hak Tanggungan, first aims to find out and analyze how disputes are resolved for flats buyers who experience law execution of their future apartment units because the land rights are secured. This is normative legal research that will explore the contents of statutory regulations. The results of this research are that several instruments exist as a unit in purchasing an apartment/flats, one of which is PPJB, the status of the buyer is as a buyer, not bezitter, eignar, or non-litigation channels with specific steps prioritize detentor, the dispute settlement mechanism according to the Agreement in the PPJB. Following statutory regulations, however, the buyer can still take the litigation route as a mechanism for settling the dispute, with compensation claims and suit for default based on the existing PPJB.Keywords: PPJB, Flat, Hak Tanggungan